2016
DOI: 10.3109/13880209.2015.1103753
|View full text |Cite
|
Sign up to set email alerts
|

Biological activity of terpene compounds produced by biotechnological methods

Abstract: Context Biotransformation systems are profitable tools for structural modification of bioactive natural compounds into valuable biologically active terpenoids. Objective This study determines the biological effect of (R)-(+)-limonene and (À)-a-pinene, and their oxygenated derivatives, (a) perillyl alcohol and (S)-(+)-and (R)-(À)-carvone enantiomers and (b) linalool, trans-verbenol and verbenone, respectively, on human colon tumour cells and normal colonic epithelium. Materials and methods Biotransformation pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…After 24 h, the cells were incubated with the NR reagent for 3 h, fixed with the NR fixative solution (1% CaCl 2 in 0.5% formalin) for 3 min at room temperature, and solubilized in 1% acetic acid in 50% ethanol under shaking for 20 min. Absorbance was measured at 550 nm using an Emax Miocroplate Reader [23].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After 24 h, the cells were incubated with the NR reagent for 3 h, fixed with the NR fixative solution (1% CaCl 2 in 0.5% formalin) for 3 min at room temperature, and solubilized in 1% acetic acid in 50% ethanol under shaking for 20 min. Absorbance was measured at 550 nm using an Emax Miocroplate Reader [23].…”
Section: Methodsmentioning
confidence: 99%
“…The activity of each extract was determined by comparing its absorbance with that of a control solution (reagents without extract) and standards. The capability to scavenge DPPH radical was calculated by the following formula: DPPH scavenging effect (%) = [(Xcontrol − Xextract/Xcontrol) × 100] where Xcontrol is the absorbance of the control and Xextract is the absorbance in the presence of extracts [23].…”
Section: Cell Cycle Progression -Propidium Iodide Stainingmentioning
confidence: 99%
“…In the only study in which the terpenoids were evaluated for those effects, Rufino and co‐workers found that they were less effective, or even completely inactive, as opposed to their hydrocarbon counterpart, pinene . Our own earlier finding, however, was that some monoterpene derivatives exerted a considerably higher bioactivity against human colon tumour cells in comparison with their precursor …”
Section: Discussionmentioning
confidence: 92%
“…In our previous study, we showed that certain biotransformation products of pinene ( trans ‐verbenol and verbenone) exerted stronger biological inhibitory effects against human colon tumour cells than their precursors . One serious obstacle to the wide‐scale use of these compounds in the treatment of cancer, however, was their high price.…”
Section: Introductionmentioning
confidence: 99%
“…21 α-Pinene (1) is a monoterpene found also in P. hispidum essential oil 8a and other Piperaceae species 9 and was described as insecticidal repellent 22 and cytotoxic selectively against tumor cells. 23 The linalool (15) was the major substance of inflorescences essential oil and was found in high concentration in inflorescence hydrolate but was absent or in low concentrations in the other samples, so may be thought of as a chemical marker for quality control of inflorescences. This compound shows the importance of chemical composition studies of different plant organs.…”
mentioning
confidence: 99%